1974
DOI: 10.1152/ajplegacy.1974.226.5.1088
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitivity of afferent cardiac sympathetic nerve fibers

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…As with endings asso ciated with vagal afferents, the sympathetic receptors are not a homogeneous group, but differ with regard to their location, functional characteristics, and type of afferent connection. Some receptors are tonically active and some, particularly those with medullated afferents, exhibit a cardiac rhythmicity (134,135,216). Some sympathetic receptors are attached to thin, medullated fibers (190, 216-2 18), while others have non medullated afferents (2 16, 218).…”
Section: Ventricular Receptors With Sympathetic Afferentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with endings asso ciated with vagal afferents, the sympathetic receptors are not a homogeneous group, but differ with regard to their location, functional characteristics, and type of afferent connection. Some receptors are tonically active and some, particularly those with medullated afferents, exhibit a cardiac rhythmicity (134,135,216). Some sympathetic receptors are attached to thin, medullated fibers (190, 216-2 18), while others have non medullated afferents (2 16, 218).…”
Section: Ventricular Receptors With Sympathetic Afferentsmentioning
confidence: 99%
“…While, as mentioned, some endings are located in the atria, most art> concentrated in the ventricles (134). Many endings both with medullated and with nonmedullated afferents are mechano sensitive, responding to touch and probing of the ventricular wall (23, 77,216,219) and to increased pressure or distention of the ventricles (77,132,134), for example, in response to transfusions and increased,outfl ow resistance. Some receptors are tonically active and some, particularly those with medullated afferents, exhibit a cardiac rhythmicity (134,135,216).…”
Section: Ventricular Receptors With Sympathetic Afferentsmentioning
confidence: 99%
“…The afferent fibres from such receptors travel in the sympathetic nerves towards the central nervous system. [16][17][18] It has been demonstrated that stimulation of the sympathetic afferent fibres produces reflex inhibition of vagal efferent activity. 19 Therefore, sympathetic block by TEA can increase cardiac vagal efferent activity and, thereby, decrease heart rate and prolong AV nodal impulse conduction and refractoriness.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic and parasympathetic afferent nerve activity originating from receptors within the heart have been described by Armour (1), Hess et al (6), Hey mans and Neil (7), Kostreva et al (11), Malliani et al (15), Uchida et al (25) and Veda et al (26). The anatomical distribution of cardiac afferent and efferent neural pathways and some of their reflex roles have been studied by Armour (1), Malliani et al (13), Mizeres (16), Randall (19) and Randall et al (20).…”
Section: Introductionmentioning
confidence: 99%